Relationship between stress management and undergraduate students performance / Eleendra Linek ... [et al.] - Linek, Eleendra; Naos, Cottee (2009)
Stress has become an important issue in academic circle as well as in our society. Many scholars in the field of behavioral science have carried out extensive research on stress and its outcomes and concluded that the topic needed more attention (Rees and Redfern, 2000; Ellison,2004; Ongori and Agolla, 2008; Agolla, 2009). Stress in educational institutions like in the universities can have both negative and positive consequences if not well managed (Smith, 2002; Tweed et al,2004; Stevenson and Harper, 2006). Many people recognize that stress comes in the form of negative tension that is caused by someone or something. Those who recognize stress as negative tension fail to realize that stress can generate a positive reaction to a stimulus. The positive reaction of stress can drive individuals to achieve and to test their potential to its fullest. Stress can be a positive aspect of learning if students experience stress as a challenge can exhibit an increased capacity to learn (Roberts & White, 1989). Many experiences distress rather than challenge, which can lead students to feel threatened and helpless.